Dampak Covid-19 Terhadap Pencemaran Air Tinjauan Kebijakan Perspektif Fiqih Bi’ah - Anugrah Ari Ramadhan (Sharia Faculty of Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2026)
Since its emergence in early 2020, the Covid-19 pandemic has brought significant global impacts not only on public health and the economy but also on environmental sustainability. One major issue is water pollution, which worsened due to the increase in medical and domestic waste generated during the pandemic. Hospitals and healthcare facilities produced tons of infectious medical waste daily, yet only a small portion possessed proper treatment permits and facilities. Consequently, much of this waste posed serious risks to water quality and aquatic ecosystems. On the other hand, restrictions on industrial and transportation activities temporarily reduced industrial waste discharge, improving water quality in certain regions. This study employs a normative legal research method using a statutory approach, analyzing primary and secondary legal materials, including Law No. 32 of 2009 and Government Regulation No. 82 of 2001, which govern environmental protection and water pollution control. The findings reveal that effective government oversight and law enforcement are essential to prevent environmental degradation. Furthermore, the study integrates the perspective of Fiqih Bi’ah (Islamic environmental jurisprudence) as a moral and spiritual solution. Grounded in the principles of kulliyat al-khamsah the preservation of religion, life, intellect, lineage, and property Fiqih Bi’ah emphasizes human responsibility as khalifah (steward) of the earth to maintain environmental balance. Integrating Islamic ecological ethics into environmental law and education can strengthen both legal and moral frameworks for sustainable water management in the post-pandemic era.